Gagasan Pembaruan dalam Bidang Hukum Kewarisan - Haries, Akhmad (Mazahib, 2014)
As a result of intellectual work through istinbat or ijtihad of the scholars in understanding the provisions of paragraph al-Quran and al-Sunnah, Fiqh Mawaris has been stated in detail in the books of fiqh. However, social development and habits that occur and grow in the awareness of the public law, gave birth to the ideas of reform in the field of inheritance law. These ideas need to be studied, so that the message of Mohammad who believed sa>lihun likulli Zama>n wa maka>n be realized. The ideas of this update includes the division of inheritance based faraid is{la<h, the implementation of the grant, the division of inheritance based on consultation and consensus (is} lah), and the division of joint property. Although the ideas of reform in the field of inheritance law is normatively different from the concept of inheritance in the Qur'an and Sunnah, but the concepts deserves to be appreciated and promoted, because realistic and fair.